Responses of Green Lettuce (Lactuca Sativa L) Plants to the Application of Various Doses of Kasgot Pupuk (Maggot Waste) - Taopik, Ahmad; Hadiyatus Solehah, Putri Nur (Fakultas Sains dan Teknologi UIN Sunan Gunung Djati Bandung, 2025)
Utilization of vegetable waste can be done by making organic fertilizer assisted by using black soldier fly biodecomposer agents or Black Soldier Fly, the resulting fertilizer is maggot (kasgot) fertilizer. The purpose of this study was to determine the effect of organic fertilizer of vegetable waste left over from maggot (kasgot) cultivation on the growth and yield of Green Lettuce (Lactuca sativa L) plants and get the best dose of kasgot fertilizer. This research was conducted at the Technical Implementation Unit (UPT) of the Food Security and Livestock Service Office (DKPP) of Bandung City. This research was conducted from November to July 2024. The method used in this study was group design with 6 treatments with 5 replications, the treatments given were A = Soil + 100%, Urea; B = Kasgot 5 t ha -1+ 50% Urea; C = Kasgot 10 t ha -1+ 50% Urea; D= Kasgot 15 t ha -1+ 50% Urea; E= Kasgot 20 t ha -1+ 50% Urea; F= 20 Kasgot 20 t ha (-1). The results showed that fertilizing Kasgot 5 t ha(- 1) (B) gave the best results on the parameters of plant height and number of leaves of Green Lettuce plants. So fertilization with a dose of 5 t ha-1+ 50% Urea is the recommended fertilization.